STRATEGI KOMUNIKASI PROGRAM "IKOY-IKOYAN" ARIEF MUHAMMAD DI INSTAGRAM @ARIEFMUHAMMAD (E-Jurnal Medium, 2022)
This research is motivated by the facts about influencers as well as entrepreneurs who use Instagram social media and create a program called "ikoy-ikoyan" to communicate strategy as a tool or brand promotion material that is held by Arief Muhammad. Therefore, this study formulates the problem and the purpose is to find out: How is the communication strategy of Arief Muhammad's "ikoy-ikoyan" program on Instagram @ariefmuhammad. The results of this research show that the way communication is made by Arief Muhammad is a directed communication strategy and includes communication components with indicators (communicator, audience, message, media and effects). The benefits obtained by Arief Muhammad are advantages in obtaining leads, increased engagement, increased awareness, and savings in financing. Keywords: Communication Strategy, New Media, Instagram, Ikoy-ikoyan, @ariefmuhammad